Attitudes and Self-Efficacy: Perspectives on Science Subjects for Junior High School Students - M Dwi Wiwik Ernawati; Asrial Asrial; Dwi Agus Kurniawan; Wahyu Adi Pratama; Rahmat Perdana; Rahmi Rahmi (Universitas Pendidikan Ganesha, 2021)
Physics is one of the subjects considered heavy and avoided by some students, which is very challenging, frustrating, perseverance, perseverance, thoroughness and lots of practice so that in reality, not many students like physics. This study aims to determine the differences and the relationship between students' attitudes and self-efficacy in learning science. This type of research is quantitative with a comparative type. The number of respondents used as a sample is 74 students. The data collection technique used simple random sampling. The study results using the T-test showed significant differences in students' attitudes and self-efficacy in science lessons, both female and male students in grade 8A and grade 8B. The correlation test results between students' attitudes and self-efficacy towards science subjects in grade 8A showed that the second variable (attitude and self-efficacy) was related. Moreover, the correlation test results in class 8B showed that the two variables (attitude and self-efficacy) were related. The urgency of this research is that teachers can find out the differences in attitudes and self-efficacy between male and female students. Compared to previous research, the novelty of this study is to use Attitude and self-efficacy variables, with different indicators from previous studies.